Implementation Of Youtube Channel in Distance Micro-Teaching Learning - Ajat Sudrajat; Ojat Darojat; DarsiharjoUni Darsiharjo; Lisa Dwi Ningtyas (Buana Pendidikan, 2023)
Some regions in Indonesia are still in the top, remote, and underdeveloped categories. In order to support the quality of learning that can reach all re-gions, learning videos are used through the YouTube channel. This research is an experimental study with a quasi-experimental design with the match-ing-only pretest-posttest as the experimental design. The research sample consisted of 60 students, with 30 students as the control class (the group of students who were not given the product) and 30 students as the treatment class (the group of students who were given the product). The results are that YouTube videos are still effectively used to improve students' basic abilities. It is recommended that lecturers who teach micro-teaching courses use learning videos on the YouTube channel to support improving stu-dents' micro-teaching skills.